Does Poverty in a Scandinavian Welfare State Influence School Competence in Adolescents?. Issue 3 (September 2015) - Johnsen, Anja; Iversen, Anette Christine; Lie, Stein Atle; Sandbæk, Mona
<x xml:space="preserve">Abstract</x> This study aims to investigate the relationship between poverty, parental socioeconomic status, and adolescent self‐perceived school competence. The study is a prospective cohort study in which the low‐income group consists of 261 adolescents 12–18 years of age whose family income was below the EU poverty line in 2005–2007, whereas the control group consists of 248 adolescents 12–18 years of age whose family income was drawn from all income groups. School competence was assessed from adolescents' self‐reports. This study finds no significant difference in school competence between the low‐income and the control group. However, when splitting the low‐income group into (a) "Norwegian adolescents" and (b) "Immigrant adolescents, " the "Immigrant adolescents" reported school competence similar to the control group. The "Norwegian adolescents" in the low‐income group reported the lowest school competence. To test whether age influences school competence, adjusted linear models were run for the sample when grouped into adolescents 12–15 years and adolescents 16–18 years of age. Among the younger adolescents in the comparison group, having a father with higher education was positively related to school competence. Of those 16–18 years of age, boys in the low‐income group exhibit higher school competence than girls.